Highlighting Protective Effect of Encapsulation on Yeast Cell Response to Dehydration Using Synchrotron Infrared Microspectroscopy at the Single-Cell Level - Nguyen, Thanh Dat; Guyot, Stéphane; Pénicaud, Caroline; Passot, Stéphanie; Sandt, Christophe; Fonseca, Fernanda; Saurel, Rémi; Husson, Florence (Frontiers in Microbiology, 2020)
In the present paper, the Layer by Layer (LbL) method using β-lactoglobulin and sodium alginate was performed to individually encapsulate Saccharomyces cerevisiae yeast in microorganized shells in order to protect cells against stress during dehydration. For the first time, the potentiality of Synchrotron-Fourier Transform InfraRed microspectroscopy was explored at the single-cell level in order to analyze the contribution of the biochemical composition of non-encapsulated versus encapsulated cells in response to dehydration. hhh. The encapsulation process could generate stresses that involve beneficial biochemical modification at lipid level. The capsule could be a barrier that reduces the kinetics of water transfer through cell membrane and also diminishes damages induced. Further work coupling biochemical and physiological analysis following different kinetic of dehydration/rehydration on a higher number of cells would improve knowledge on the role of microorganized shells on yeast resistance and on the biochemical single-cell modifications associated